Supply Chain - innovation: past, present, and future - Seyhan, Mehmet; Çiğdem, Şemsettin; Yildiz, Bülent; Meidutė-Kavaliauskienė, Ieva (Independent Journal of Management and Production, 2021)
Nowadays, one of the factors that enable businesses to adapt to markets that are constantly renewed and changing due to the ever-increasing flow of information, and perhaps the most important, is innovation. Innovation is a topic that is frequently studied by both markets and academics. However, the increase in the quantity of studies conducted is far from meeting the need in this field. As a result of the shortening of product life cycles in current market conditions, companies are obliged to continuously innovate in order to sustain their existence. Increasing raw material and resource diversification requirement due to the increasing need for innovation made it necessary to examine and understand the supply chain in the context of innovation. The importance of innovation, especially in the case of participation by suppliers in innovation for a competitive advantage, has resulted in many in-depth studies published in research papers in the field. In this study, articles published in the Web of Science database between 1996-2020 and covering the topics of  supply chain and innovation were analyzed in order to reveal the patterns of supply chain management and innovation research, identify relative deficiencies and provide some guidelines. For this purpose, a systematic literature review and bibliometric analysis related has been made. It has been possible to determine the effective actors in the field by including the distribution of the concepts in question according to time, countries, universities and journals. In addition, as a result of the keyword analysis, the evolution and open points of the field over time are among the findings of the study.
Keywords: Supply Chain; Bibliometric Analysis; Thematic Evolution; Innovation; Systematic Literature Review; 9. Industry and infrastructure